1984
DOI: 10.1063/1.447165
|View full text |Cite|
|
Sign up to set email alerts
|

ΔM j transitions in homonuclear molecule scattering off corrugated surfaces. Square and rectangular lattice symmetry and purely repulsive interaction

Abstract: In this paper, we present the first formal and computational studies of Δmj transitions occurring in homonuclear molecule-corrugated surface collisions. The model potential is a pairwise additive one which correctly incorporates the fact that Δmj transitions occur only for corrugated surfaces (provided the quantization axis is chosen to be the average surface normal). The principal results are: (a) Δmj transitions are extremely sensitive to lattice symmetry; (b) strong selection rules obtain for specular scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…To understand the origin of the discrepancy between the DFT based calculations and the data, we look at the calculated 𝑆-matrix elements shown in Table 1, which predict that only the mJ=0 state undergoes de-excitation with a significant probability, in line with an approximate ∆mJ=0 propensity rule. This prediction has also been seen in previous calculations of RID transitions on square lattices 26,27 . It is important to note that if there is only one nonzero element in the 𝑆-matrix, the shape of the corresponding signal becomes independent of the specific magnitude and phase of the non-zero element.…”
Section: Resultssupporting
confidence: 88%
“…To understand the origin of the discrepancy between the DFT based calculations and the data, we look at the calculated 𝑆-matrix elements shown in Table 1, which predict that only the mJ=0 state undergoes de-excitation with a significant probability, in line with an approximate ∆mJ=0 propensity rule. This prediction has also been seen in previous calculations of RID transitions on square lattices 26,27 . It is important to note that if there is only one nonzero element in the 𝑆-matrix, the shape of the corresponding signal becomes independent of the specific magnitude and phase of the non-zero element.…”
Section: Resultssupporting
confidence: 88%
“…The measurement of such a large change in the alignment would confirm that Δ m j ≠ 0 transitions occur with large probability: the minimum value of the alignment of the scattered j = 2 molecules is −0.96 if P ( j =2, m j =0→ j ‘=2, m j ‘≠0) ≤ 1%. Such low values for Δ m j ≠ 0 transitions were found for our model potential excluding V els , and also in the model calculations on H 2 −surface scattering referred to above which also excluded V els , as long as realistic values were used for the values of the surface lattice constants. The measurement of a large change in the alignment of the scattered molecules would therefore also serve as further proof for the importance of the electrostatic interaction for the scattering.…”
Section: Scattering Of H2 From Lif(001)supporting
confidence: 71%
“…In previous calculations on scattering from ( j =1, m j ) states, we have shown that the probabilities for Δ m j ≠ 0 transitions decrease to less than 1% when the electrostatic interaction is excluded from the model. , Previously, calculations on scattering of homoatomic diatomic molecules using model potentials excluding V els only predicted large probabilities for Δ m j ≠ 0 transitions for cases in which the molecular bond length was close to the surface lattice constant. , As already noted before, the fact that V els is expressed in all second-order spherical harmonics (see eq 3.2) already suggests the possibility of large probabilities for Δ m j ≠ 0 transitions. As shown elsewhere, the reason that such transitions are primarily caused by V els is that it contributes φ-dependent terms that are both longer ranged and larger in the classically allowed region than the other components making up the molecule−surface interaction.…”
Section: Scattering Of H2 From Lif(001)mentioning
confidence: 54%
See 1 more Smart Citation
“…Coauthors on the paper are Yinnon, a previously mentioned graduate student, and John Murrell, a well-known theorist from the University of Sussex who visited us then. We also derived useful approximations for rotationally inelastic and vibrationally inelastic molecule-surface scattering (18)(19)(20). These projects were done in cooperation with Donald J. Kouri of the University of Houston, a good friend and a collaborator of many years.…”
Section: Molecular Scattering From Surfacesmentioning
confidence: 99%